2022
DOI: 10.1007/s11657-022-01099-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction prevalence of fragility fracture hospitalisation during the COVID-19 lockdown

Abstract: Fracture hospitalizations of people ≥ 65 years old living in France increased annually from 2015 until 2019 (average: 1.8%), until being reduced in 2020 (− 1.4%) with an abrupt decrease during the lockdown period. Decreased exposure to the risk of falling during COVID-19 year 2020 may have reflected in lower incidence of fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Furthermore, the trends in this analysis are likely to be conservative estimates as a result of incorporating the years in which the COVID-19 pandemic had the greatest impact (2020 and 2021). Previous reports have clearly illustrated the drastic reduction in hospitalizations for geriatric fractures and in TKAs and THAs during this time period 25-28 . Consequently, the observed and predicted trends of periprosthetic fractures are likely to have been underestimated in this study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Furthermore, the trends in this analysis are likely to be conservative estimates as a result of incorporating the years in which the COVID-19 pandemic had the greatest impact (2020 and 2021). Previous reports have clearly illustrated the drastic reduction in hospitalizations for geriatric fractures and in TKAs and THAs during this time period 25-28 . Consequently, the observed and predicted trends of periprosthetic fractures are likely to have been underestimated in this study.…”
Section: Discussionmentioning
confidence: 64%
“…The shaded area indicates projected values, with the error bars representing the 95% CI of each value. hospitalizations for geriatric fractures and in TKAs and THAs during this time period [25][26][27][28] . Consequently, the observed and predicted trends of periprosthetic fractures are likely to have been underestimated in this study.…”
Section: Discussionmentioning
confidence: 95%
“…A review of the literature identified several studies demonstrating a decrease in orthopaedic trauma cases during the lockdown 1,2,4-8 with just a few studies focusing solely on the older demographic. 2,[5][6][7] The study by Barreto et al revealed a decrease in the number of fracture hospitalisations of older people throughout the COVID year (2020). 2 According to Fadi et al, the proportion of geriatric patients with hip fractures in the lockdown group was considerably greater than in the non-lockdown group, while the overall number of trauma patients was lower.…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7] The study by Barreto et al revealed a decrease in the number of fracture hospitalisations of older people throughout the COVID year (2020). 2 According to Fadi et al, the proportion of geriatric patients with hip fractures in the lockdown group was considerably greater than in the non-lockdown group, while the overall number of trauma patients was lower. Although the frequency of hip fractures was lower in our research during the nonlockdown phase and considerably lower during the lockdown period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation